The Influence of Corporate Social Responsibility (CSR) and Environmental Social Governance (ESG) Disclosure on Profitability in Companies in the IDX ESG & IDX HIDIV20 Sector from 2020 to 2023 - Wijaya, Hans Darma; Iryanto, Budi Widiyo (Jurnal Indonesia Sosial Sains, 2024)
This research aims to analyze and evaluate the effect of Corporate Social Responsibility (CSR) and Environmental Social Governance (ESG) disclosures on corporate profitability. The focus of this study is to identify how CSR and ESG practices disclosed by companies affect key profitability indicators such as Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM). The object of research is companies listed on the Indonesia Stock Exchange, including IDX ESG Leaders Index (IDX ESG LID) and IDX High Dividend 20 (IDX HIDIV20) in 2020-2023; the sample is 25 companies. In this study, the analysis technique used was Structural Equation Modeling (SEM) PLS conducted using the WARP PLS (Weighted Autoregressive Distributed Lag PLS) method. The results showed that CSR disclosure has a positive and significant influence on corporate profitability, while ESG disclosure has a negative and significant influence. The study's implications suggest that CSR implementation can enhance financial performance, whereas ESG disclosure, despite offering long-term benefits, often requires significant initial investment, which can reduce short-term profitability.